Discussion of constructing unified DPI system by operators in the background of big data - Huifang HOU; Jie PAN (Dianxin kexue)
Mobile data traffic increases gradually.Operator's business model is transferring from “telephone traffic management” to “traffic management”.Big data management will become the main development direction of operators.For big data management,operators explore the value and application of DPI technology and make the unified DPI system standards to offer comprehensive and standard traffic data.The insufficiency of traditional DPI deployment mode was analyzed,and the unified DPI system to offer basic data security for accelerating development of big data was presented.